Using Web Conferencing Environment for Teaching and Learning Process in Library and Information Science in India during COVID-19: A Study - Aich, Laltu; Banerjee, Swapna (Qualitative and Quantitative Methods in Libraries, 2022)
Webinars in Library and Information Science are on the rise during the COVID-19 period. This is much more visible in the Indian scenario. This article gives a glimpse of the number & types of webinars in LIS from April 2020 to June 2021. The designation and gender of resource persons, the platforms of organization hosting these webinars, the frequency of the webinars and the subject matters of these webinars have all been focused clearly here. This article therefore points towards the direction the subject Library and Information Science is heading and specially its design and ramifications in India.